Analysis Of Employee Attitudes And Behavior In Waste Management At The Environmental Services Department Of Gunungsitoli City - Ley, Demas Agatha; Zega, Yamolala; Telaumbanua, Eliagus; Lahagu, Palindungan (Sekolah Tinggi Ilmu Ekonomi Amkop Makassar, 2026)
This research examines employee attitudes and behavior in waste management at the Environmental Agency of Gunungsitoli City. Using a qualitative approach, data were collected from four key informants through in-depth interviews, observation, and documentation. The informants included the Head of the Environmental Agency, Head of Waste Management Division, Head of General Affairs and Personnel Sub-division, and Environmental Impact Controller. Data analysis employed the Miles and Huberman model, encompassing data collection, data reduction, data presentation, and conclusion drawing. Results indicate that employee attitudes in waste management are generally positive, characterized by strong commitment to compliance with regulations, emphasis on integrity and transparency, and implementation of systematic educational programs and strict supervision. Employee behavior demonstrates high performance through proper task execution, enhanced social relationships among employees through work group activities, comprehensive training programs, transparent performance evaluations, and motivation initiatives to increase employee confidence. However, several challenges persist, including minimal public awareness of environmental cleanliness, limited facilities and infrastructure such as insufficient waste transport trucks and inadequate final disposal sites (TPA), lack of clear standard operating procedures for waste management, and insufficient coordination among relevant parties. These findings emphasize the necessity for strengthening waste management practices through enhanced public education, infrastructure improvements, establishment of clear operational procedures, and improved inter-agency coordination to achieve sustainable waste management in Gunungsitoli City.